Dielectric properties of nematic liquid crystals with Fe₃O₄ nanoparticles in direct magnetic field - Gornitska, O.P.; Koval’chuk, A.V.; Koval’chuk, T.N.; Kopčanský, P.; Timko, M.; Zavisova, V.; Koneracká, M.; Tomašovičová, N.; Jadzyn, J.; Studenyak, I.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Researched within the frequency range 10⁻¹–10⁶ Hz were dielectric properties
of pure 6CHBT liquid crystals and 6CHBT ones with the impurity of Fe₃O₄ nanoparticles
that have the mean diameter 5 nm and weight concentration 10⁻⁴ %. The study was
performed without and under the influence of direct magnetic field with the induction
0.45 and 0.60 T. It has been shown that the magnetic field influences on the parameters
of the near-electrode area of liquid crystal. In the case of liquid crystal with magnetic
nanoparticles, the parameter changes caused by the magnetic field depend on the
induction value.